Descriptive study of carers' support, encouragement and modelling of healthy lifestyle behaviours in residential out‐of‐home care - Rachael Cox; Helen Skouteris; Matthew Fuller‐Tyszkiewicz; Amanda D. Jones; David Gallant; Stella Omerogullari; Robyn Miller; Louise L. Hardy (Elsevier, 2015)
Abstract Objective: Given the high prevalence of overweight/obesity among young people in residential out‐of‐home care (OOHC), and as their carers are in loco parentis, this research aimed: 1) to examine the healthy lifestyle cognitions and behaviours of residential carers; and 2) to describe resources needed to improve diet and/or physical activity outcomes for residents. Methods: Cross‐sectional data were collected from 243 residential carers. Measures included: demographics; knowledge of dietary/physical activity recommendations; self‐reported encouragement/importance of health behaviours; physical activity/screen time (at work); unit 'healthiness'; and necessary resources for creating a healthy environment. Results: Staff placed importance on the residents eating well and being physically active. However, examination of carer knowledge found significant gaps in staff education. Three key priority areas were identified to help build a healthy food and activity environment in residential OOHC: funding, professional development and policy. Conclusion: Carer knowledge of healthy lifestyles can be improved and they need to be well resourced to ensure children in public care settings live in a healthy environment. Implications: These findings may inform the development of ongoing professional development to improve carers' health literacy, as well as policy to support dietary/activity guidelines for the OOHC sector.